O descontrole já está formado : tédio, identidade, violência e cultura de arquibancada - Silva, Guilherme Baziewicz de Carvalho e (2017)
The present work, adopting the line of research in violence, crime and public safety, proposes to analyze the phenomenon of cultural assimilation by gaúchos groups of football supporters, of the argentinean matrix football supporters groups of style culture, specifically of the style groups nominated as barras, and assimilated in the common sense as barras bravas, holders of a moral and conduct code based in violence, the aguante, from the style group known as Geral of Grêmio, football fans linked to the football club Grêmio Foot-Ball Porto Alegrense. In order to do so, a detailed exposition of the roots, practices, customs, rituals and cultural artifacts of the argentinean barra groups will be carried out, through a bibliographical review of social anthropology research carried out in that country. Based on the ethnographic work carried out with Geral of Grêmio, which adopted the methodological paradigm of the concepts of liquid and instant ethnography developed by cultural criminology, while referring to a necessary allusion to the geographic peculiarities and socio-cultural appropriations that made this phenomenon possible for the gaúchos groups of football supporters. Especially the process of mythological construction of the gaucho warrior ideology. The Geral of Grêmio is also different from the other style groups of the global football culture. With regard to analytical criminological content, a hypothesis based on the transcendence of boredom is erected, which the daily routine surrounded by ontological insecurity, relative deprivation, and increasing demands for the satisfaction of individualism, impose on individuals in the globalized society of late modernity, from an individual sensory experience of excitement and self-control, alternative to formal social control, by the mediated "uncontrolled", in the performance of limit-activities conceptualized in cultural criminology as edgework. These conceptualizations would not have been possible without the previous contribution of the aggregate analyzes of social disorganization and lack of formal values already evidenced by Émile Durkheim and the functionalist school of Chicago, much like William Thomas and Robert Merton, keeping the due differences of time and space. Merton is conjugated to the seduction and excitation factors inherent in the offending act observed by Jack Katz, according with the Jock Young's work, and Thomas makes it possible to explain the interweaving between the customs of the Argentinean barra groups and those that existed in the gaúcho football supporters groups of style culture, linked to the organized groups of brazilian football supporters, resulting in a hybrid group, neither Brazilian, nor Argentine, but the Geral of Grêmio, who later would influence other groups of style of the gaúcho football supporters groups of style culture, and be a reference for creating alento groups of football supporters in the rest of the country.